Elite and Popular Religion: The Case of Newman - Fenlon, Dermot (Studies in church history, 2006)
Among the signal insights of twentieth-century scholarship was the recognition that early Christianity accorded personal importance to the plebs. First, Eric Auerbach analysed the humble speech forms of early Christianity, contrasting them with the literature of learned pagans. The point was developed by Ramsay MacMullen in an important essay entitled ‘Sermo humilis’. Arnaldo Momigliano applied these insights to the theologians, historians and hagiographers of the fourth and fifth centuries. He showed how Augustine, Jerome, Socrates, Sozomen, and Theodoret of Cyr succeeded, as pagan intellectuals had not succeeded, in ‘abolishing the internal frontiers between the learned and the vulgar’. Finally, Peter Brown, in a series of brilliant works from The Cult of the Saints to his revised biography of Augustine, supplied a means of discerning in the practice of universal baptism the ‘antidote’ to the exaggerations of fourth-century ascetical elitism. Augustine imparted to the Western Middle Ages a confidence in the power of sacramental grace as efficacious not only for the ascetic few, but as communicating to the many a capacity for growth in charity, purity, and prayer. Such a perspective on the religion of the many bids adieu to Gibbon’s story of ‘philosophy’ collapsing into ‘barbarism and religion’; to Hume’s account of the superstitious and the credulous; and to Henry Hart Milman’s Romantic brand of Liberal Anglicanism as marked by ‘condescension’ towards ‘popular religion’ occluding ‘the thought processes of the average man’; a habit of mind to which Peter Brown surprisingly appended the name of Newman.